Coherent Detection of MIMO LoRa With Increased Data Rate - Luca Rugini; Keya Sardar; Giuseppe Baruffa (IEEE Open Journal of the Communications Society, 2024)
This paper proposes a Long Range (LoRa) chirp transmission scheme with multiple transmit and receive antennas. The main goal is to increase the data rate of LoRa using multiple-input multipleoutput (MIMO) spatial multiplexing. Several coherent detectors are proposed and compared in terms of performance, assuming a channel with flat Rayleigh fading and additive white Gaussian noise. By leveraging on a convenient matrix-vector model, we show that the maximum-likelihood (ML) detector can be obtained with low complexity, when the number of transmit antennas is two or three. When the number of transmit antennas is four or five, we propose a transmission scheme that permits a near- ML detection with reduced complexity. We also propose linear and widely linear detectors that exploit the signal sparsity in the chirp domain. Simulation results confirm the effectiveness of the proposed MIMO LoRa transmission schemes and detectors. Simulated results also include the effect of imperfect synchronization and channel estimation errors on the proposed coherent detection.